Soy protein isolate/bioactive glass composite membranes: processing and properties - Tansaz, Samira; Schulte, Matthias; Kneser, Ulrich (European polymer journal, 2018)
Composite biomaterials based on proteins and inorganic fillers are highly attractive for wound dressing applications due to their highly absorbent properties towards blood and exudate provided by the inorganic fillers. Moreover, such composites offer a desirable environment for cells due to the combination of organic and inorganic characteristics. This study highlights the fabrication of soy protein isolate/nanoscale bioactive glass composite films by solvent casting method as a matrix for wound-dressing applications. The effect of the addition of bioactive glass nano particles on blood clotting was assessed. Cytotoxicity and in vitro cytocompatibility of the films were also tested. The results showed that the composite films could meet the essential requirements for an appropriate wound dressing with additional favorable properties such as hemostatic capability and mechanical properties as well as significant cell cytocompatibility.